Experimental investigation and seismic response behavior of a self-centering precast concrete frame with hysteretic dampers. (1st August 2021) - Geng, Fangfang; Ding, Youliang; Wu, Honglei; Cai, Xiaoning; Zhang, Yun
Highlights: Seven cyclic loading tests on three full-sized novel SCPC beam-column connections. Compare the numerical simulation results and experimental results for novel connection. The elastoplastic dynamic responses of a novel frame at the design-basis earthquake (DBE) and the maximum considered earthquake (MCE) levels. The seismic fragility analysis of the novel SCPC frame with replaceable hysteretic dampers. Abstract: A new type of self-centering precast concrete (SCPC) frame with hysteretic dampers is developed to obtain sufficient self-recovering and energy consumption characteristics. The working principle of a novel connection is presented, and seven cyclic loading tests with different parameters on three full-sized novel beam-column joints are investigated. Adequate seismic performances were experimentally observed in cyclic loading tests. Numerical simulation of the novel connection was performed using the OpenSees software. The elaborate simulation results and test results were well matched, such as the hysteretic behaviors, prestressed tendons forces, energy consumption and self-recovering characteristics. Furthermore, a prototype structure was modeled, and the elastoplastic dynamic responses at the design-basis earthquake (DBE) and the maximum considered earthquake (MCE) levels were studied. The results showed that the peak and residual interstory drifts ( θmax and θr, max ) achieved desirable demands. The post-tensioned strands avoided excessive yielding at the MCE level, and the novel frame had an adequate energy consumption behavior. In addition, incremental dynamic analysis and vulnerability analysis were performed. The 50-year exceedance probabilities of the Immediate occupancy (IO) and Repairable (RE) limit states taking θmax and θr, max as the evaluation indicators were also calculated, respectively. The results demonstrate that the novel frame has adequate seismic performance, greater reliability and less damage potential than the traditional self-centering precast concrete (SCPC) frame without energy dissipation devices.